Peran Mahasiswa Prodi PGMI UMRI Dalam Percepatan Penyelasaian Tahfidz Juz 30 Siswa SD Muhammadiyah 5 Pekanbaru - Salman, Salman; Zahzia Kurnia Putri; Jihan Annisa Zarah; Lannuria; Humaysah; Miftahul Jannah; Muhammad Ibnu Haikal (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
The purpose of the community service activity is to recognize how students of the Elementary Madrasah Teacher Education Study Program (PGMI) of the University of Muhammadiyah Riau (UMRI) can help students of Muhammadiyah Elementary School 05 Pekanbaru in accelerating the completion of memorization of Juz 30 and applying the talaqqi and murojaah methods. This community service uses a field survey method, a program for implementing the talaqqi and murojaah methods and involves elementary school students in grades 4-6, the results of this community service show very good achievements in completing the memorization of the Qur'an, students in grades 4-6 completed 80%, this indicates that students of Muhammadiyah Elementary School 5 Pekanbaru are able to complete memorization of Juz 30 in 2 months with the method activities applied by PLP students of the PGMI study program, Muhammadiyah University of Riau.